Papers of the forty-seventh Algonquian Conference = Actes de quarante-septiéme Congrès des Algonquinistes - Macaulay, Monica; Noodin, Margaret (Papers of the Algonquian Conference Ser., 2018)
Papers of the Algonquian Conference is a collection of peer-reviewed presentations from an annual international forum that focuses on topics related to the languages and cultures of Algonquian peoples. This series touches on a variety of subject areas, including anthropology, archaeology, education, ethnography, history, Indigenous studies, language studies, literature, music, political science, psychology, religion, and sociology. Contributors often cite never-before-published data in their research, giving the reader a fresh and unique insight into the Algonquian peoples and rendering these papers essential reading for those interested in studying Algonquian society.